Coastal pH variability and the eco-physiological and behavioural response of a coastal fish species in light of future ocean acidification - Edworthy, Carla (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2021)
Ocean acidification (OA) is a global phenomenon referring to a decrease in ocean pH and a perturbation of the seawater carbonate system due to ever-increasing atmospheric CO2 concentrations. In coastal environments, identifying the impacts of OA is complex due to the multiple contributors to pH variability by coastal processes, such as freshwater inflow, upwelling, hydrodynamic processes, and biological activity. The aim of this PhD study was to quantify the local processes occurring in a temperate coastal embayment, Algoa Bay in South Africa, that contribute to pH and carbonate chemistry variability over time (monthly and 24-hour) and space (~10 km) and examine how this variability impacts a local fish species, Diplodus capensis, also commonly known as 'blacktail'. Algoa Bay, known for its complex oceanography, is an interesting location in which to quantify carbonate chemistry variability. To assess this variability, monitoring sites were selected to coincide with the Algoa Bay Sentinel Site long-term ecological research (LTER) and continuous monitoring (CMP) programmes. The average pH at offshore sites in the bay was 8.03 Â± 0.07 and at inshore sites was 8.04 Â± 0.15. High pH variability (~0.55"“0.61 pH units) was recorded at both offshore (>10 m depth) and inshore sites (intertidal surf zones). Many sites in the bay, especially the atypical site at Cape Recife, exhibit higher than the average pH levels (>8.04), suggesting that pH variability may be biologically driven. This is further evidenced by high diurnal variability in pH (~0.55 pH units). Although the specific drivers of the high pH variability in Algoa Bay could not be identified, baseline carbonate chemistry conditions were identified, which is necessary information to design and interpret biological experiments. Long-term, continuous monitoring is required to improve understanding of the drivers of pH variability in understudied coastal regions, like Algoa Bay. A local fisheries species, D. capensis, was selected as a model species to assess the impacts of future OA scenarios in Algoa Bay. It was hypothesized that this temperate, coastally distributed species would be adapted to naturally variable pH conditions and thus show some tolerance to low pH, considering that they are exposed to minimum pH levels of 7.77 and fluctuations of up to 0.55 pH units. Laboratory perturbation experiments were used to expose early postflexion stage of D. capensis to a range of pH treatments that were selected based on the measured local variability (~8.0"“7.7 pH), as well as future projected OA scenarios (7.6"“7.2 pH). Physiological responses were estimated using intermittent flow respirometry by quantifying routine and active metabolic rates as well as relative aerobic scope at each pH treatment. The behavioural responses of the larvae were also assessed at each pH treatment, as activity levels, by measuring swimming distance and speed in video-recording experiments, as well as feeding rates. D. capensis had sufficient physiological capacity to maintain metabolic performance at pH levels as low as 7.27, as evidenced by no changes in any of the measured metabolic rates (routine metabolic rate, active metabolic rate, and relative aerobic scope) after exposure to the range of pH treatments (8.02"“7.27). Feeding rates of D. capensis were similarly unaffected by pH treatment. However, it appears that subtle increases in activity level (measured by swimming distance and swimming speed experiments) occur with a decrease in pH. These changes in activity level were a consequence of a change in behaviour rather than metabolic constraints. This study concludes, however, that based on the parameters measured, there is no evidence for survival or fitness related consequences of near future OA on D. capensis. OA research is still in its infancy in South Africa, and the potential impacts of OA to local marine resources has not yet been considered in local policy and resource management strategies. Integrating field monitoring and laboratory perturbation experiments is emerging as best practice in OA research. This is the first known study on the temperate south coast of South Africa to quantify local pH variability and to use this information to evaluate the biological response of a local species using relevant local OA scenarios as treatment levels for current and near future conditions. Research on local conditions in situ and the potential impacts of future OA scenarios on socio-economically valuable species, following the model developed in this study, is necessary to provide national policy makers with relevant scientific data to inform climate change management policies for local resources.
Keywords: Ocean acidification; Diplodus capensis (Blacktail); Diplodus -- South Africa -- Algoa Bay; Diplodus -- Metabolism; Diplodus -- Food; Diplodus -- Larvae; Marine ecology -- South Africa -- Algoa Bay; Carbon dioxide -- Physiological effect; Respiration -- Measurement